Fungsi wirid surah Al-hajj ayat 27 dan surah Ali Imran ayat 9 di pondok pesantren darul huffadz almatin Sukabumi : Analisis fungsionalismr Bronislaw Malinowski - Ummah, Fadlah Nur (IIQ An Nur Yogyakarta, 2024)
In dealing with phenomena and problems that exist in diverse social life, proof is required. The Qur'an then comes as a life guide for Muslims which becomes an answer to every problem of human life. One form of living Qur'an at Darul Huffadz Al-Matin Islamic Boarding School Sukabumi is the practice of reading the wirid of Surah Al-Hajj Verse 27 And Surah Ali Imran Verse 9 as a religious ritual that is read repeatedly which becomes a routine activity. This research is a field research, by using qualitative methods. While the data analysis technique uses Bronislaw Malinowski's functionalism theory. The result of this study are that reading amaliah is a form of tabarruk caregivers taken from verses of the Qur’an which have several functins, including: attract students, asking for protection, facilitating all affairs and hajat, being able to set foot in Makkah, adding a sense of enthusiasm and asking for improved quality of faith. Keywords: Functionalism, Wirid, Malinowski